Associations between anxiety, depression, and risk of suicidal behaviors in Chinese medical college students - Li, Jia; Zhang, Yaru; Siu Man Chan, Bella; Tan, Sun Nee; Lu, Jianping; Luo, Xuerong; Shen, Yanmei; Zhang, Xiang Yang (Frontiers in Psychiatry, 2022)
Background Previous studies have established a strong association between depression and suicidal behaviors, yet the relationship between anxiety and suicidal behaviors remains unclear. This study examines whether anxiety and depression are independent risk factors for suicidal behaviors in medical college students, and further, whether anxiety may increase the greater risk of suicidal behaviors (SB) in participants with depression. Methods This cross-sectional study was conducted among 4,882 medical students. Demographic information, anxiety, and depression data were collected using online questionnaires or through a widely used social media app named WeChat. Results Anxiety and depression were independent risk factors for suicidal behaviors, and levels of risk correlated positively with the severity of both anxiety and depressive symptoms. A dose–response relationship was identified between the severity of anxiety and the risk of SB, as well as the severity of depression and SB. Furthermore, anxiety increased the risk of suicidal behaviors in participants with depression, with a dose–response relationship between the severity of anxiety symptoms and the risk of SB. Conclusion The findings highlight the importance of screening for anxiety and depressive symptoms in medical college students, as well as reducing anxiety in addition to depressive symptoms in treatment. This study provides valuable data as a reference for clinicians for suicide risk assessments.